2000
DOI: 10.1007/s002610000092
|View full text |Cite
|
Sign up to set email alerts
|

Chronic tuberculous epididymitis: color Doppler US findings with histopathologic correlation

Abstract: Color Doppler US may be helpful for differential diagnosis of tuberculous epididymitis and non-tuberculous epididymitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
2
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 7 publications
2
20
2
1
Order By: Relevance
“…26,27 Hyperemia is seen with acute bacterial epididymitis, whereas focal linear or spotty blood flow signals may be seen in the peripheral zone of tuberculous epididymitis. 28 Sonographic findings in tuberculous orchitis are similar to those of tuberculous epididymitis. Other associated sonographic findings include thickened scrotal skin, hydrocele, intrascrotal extratesticular calcification, scrotal abscesses, and scrotal sinus tract.…”
Section: Uncommon Infectious Epididymo-orchitis Tuberculous Epididymomentioning
confidence: 71%
“…26,27 Hyperemia is seen with acute bacterial epididymitis, whereas focal linear or spotty blood flow signals may be seen in the peripheral zone of tuberculous epididymitis. 28 Sonographic findings in tuberculous orchitis are similar to those of tuberculous epididymitis. Other associated sonographic findings include thickened scrotal skin, hydrocele, intrascrotal extratesticular calcification, scrotal abscesses, and scrotal sinus tract.…”
Section: Uncommon Infectious Epididymo-orchitis Tuberculous Epididymomentioning
confidence: 71%
“…7,16 On color Doppler sonography, nontuberculous epididymitis usually shows Doppler signals within the affected epididymis, whereas tuberculous epididymitis may show at most focal linear or spotty Doppler signals at the periphery of the epididymis. 24 Yang et al 29 found evidence that color Doppler signals were less numerous at the periphery of a tuberculous epididymal abscess than at the periphery of a pyogenic one.…”
Section: Discussionmentioning
confidence: 98%
“…4,9 Sonographically, tuberculous epididymitis appears as diffusely enlarged heterogeneously hypoechoic, diffusely enlarged homogeneously hypoechoic, or nodular enlarged heterogeneously hypoechoic lesions. 2,7,15,16,24 The sonographic heterogeneity may be accounted for by the presence of various pathologic components, including caseation necrosis, granulation tissues, and fibrosis. If a sinus draining necrotic pus exists, the lesion may have a more heterogeneous appearance, 2,7,16 as in the tail of the left epididymis in our case.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that TBC of the genital system may be present 20-30 years after primary localization [5,23]. In such cases, the source of infection might be existing primary focus in the lungs or lymph nodes, rare in bones, bowels or could be endogenous reinfection or exogenous superinfection [10,24].…”
mentioning
confidence: 99%